Enhancing Critical Thinking and Physics Concept Understanding through REACT-OLabs - Ridha Vitri Suryawati; Antomi Saregar; Ajo Dian Yusandika (Universitas Lambung Mangkurat, 2026)
Students' critical thinking skills and science concepts are still lacking. This is because physics instruction tends on rote memorization, resulting in students having a superficial understanding of the material. The purpose of this study is to determine the effect of the REACT model, supported by OLabs, on students’ critical thinking skills and understanding of physics concepts. The study employed a quasi-experimental design with pretest–posttest measures and a quantitative approach. The study population consisted of 11th-grade students at SMAN 1 Seputih Banyak for the 2025/2026 academic year. A sample of 70 students was selected using cluster random sampling, comprising an experimental class (using the REACT model supported by OLabs) and a control class (conventional instruction). The instrument consists of an essay test to measure both variables, with 10 items measuring critical thinking skills and 12 items measuring conceptual understanding. The data were analyzed using a MANOVA test. The results of the study indicate that the REACT model, supported by OLabs, has an impact on both dependent variables, with a significance value of 0.000 (p < 0.05). The average score of the experimental group (77.43) for critical thinking skills surpassed that of the control group (54. 20), as did the score for conceptual understanding (83.09 > 54.51). These findings indicate that the use of a contextual learning model combined with simulation technology can help students better understand abstract physics concepts while simultaneously improving their comprehension and critical thinking skills. The conclusion of this study is that the REACT model, supported by OLabs, is effective in improving students’ critical thinking skills and understanding of physics concepts. Thus, it can serve as an innovative alternative for educators.